COMPOSTUDIO Model: an interactive method for immersive project-based learning in built environment studios - Nizarudin, Norhanis Diyana; Zakariya, Khalilah (2020)
The COMPOSTUDIO Model is formulated to improve the effectiveness of hybrid teaching and learning experience for built environment educators and students. COMPOSTUDIO consists of composite digital and non-digital methods and a comprehensive process from framing the project until delivering the solutions. The objectives of COMPOSTUDIO are, (i) to incorporate critical thinking throughout the studio process, (ii) to encourage creativity in problem-solving, (iii) to promote collaboration through immersive physical and virtual experiences, and (iv) to advance 21st century communication skills among educators and students. The COMPOSTUDIO Model enhances the existing studio approach by combining interactive and immersive offline and online methods in project-based learning that are practical, easy to use, cost-efficient and tech-savvy using readily available technology. Students found this model to be engaging and helpful to improve their creativity and soft skills. This robust model can be applied and replicated by other studios and classes beyond the built environment.